Identification of highly selective type II kinase inhibitors with chiral peptidomimetic tails. (31st December 2022) - Han, Seo-Jung; Jung, Jae Eun; Oh, Do Hee; Kim, Minsup; Kim, Jae-Min; Chung, Kyung-Sook; Han, Hee-Soo; Lee, Jeong-Hun; Lee, Kyung-Tae; Jeong, Hee Jin; Park, In Ho; Jeon, Eunkyeong; et al.
Abstract: Identification of highly selective type II kinase inhibitors is described. Two different chiral peptidomimetic scaffolds were introduced on the tail region of non-selective type II kinase inhibitor GNF-7 to enhance the selectivity. Kinome-wide selectivity profiling analysis showed that type II kinase inhibitor 7a potently inhibited Lck kinase with great selectivity (IC50 of 23.0 nM). It was found that 7a and its derivatives possessed high selectivity for Lck over even structurally conserved all Src family kinases. We also observed that 7a inhibited Lck activation in Jurkat T cells. Moreover, 7a was found to alleviate clinical symptoms in DSS-induced colitis mice. This study provides a novel insight into the design of selective type II kinase inhibitors by adopting chiral peptidomimetic moieties on the tail region.